Małżeństwa polsko-cudzoziemskie o charakterze fikcyjnym a bezpieczeństwo państwa. Przyczynek do problemu (Świat Idei i Polityki, 2013)
Fictional marriage, or marriage of convenienience, as it is defined in the legal documents of European Union, is a relatively new problem to the Polish legal system. There’s no legal definition of the issue neither in civil, nor penal law. Nevertheless with the increase of immigration in the recent year, a large number of intermarriages is being recorded. Approximately one out of five marriages is fictional, which means that the authorization of residency for a foreigner was its only purpose. What is more, these marriages are being associated with a organized crime. To combat these state security threats, both public administration and law enforcement agencies were given a special entitlements. Nevertheless the number of scientific research of jurisprudence is inadequate to the importance of the issue. Polish prosecutors’ office tend to underestimate the problem. Rulings of judiciary are inconsistent. Therefore, a changes in the Polish legal system are required.